ANALYSIS OF THE PHYTOCHEMICALS, ANTIOXIDANTS, AND ANTIMICROBIAL ACTIVITY OF FICUS TSJAHELA BURM. F LEAF, BARK, AND FRUIT EXTRACTS - V, THAMARAIKANI; S DIVYA, AMALA; T, SEKAR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Ficus tsjahela Burm. f is a medicinal tree species, endemic to the Western Ghats having various healing properties. This study focused to check the antioxidant and antimicrobial activities of the leaf, bark, and fruit samples of F. tsjahela. Methods: The plant samples were subjected to Soxhlet extraction for phytochemical analysis and further experimental studies. The test on phytochemical studies indicated the presence of alkaloids, saponins, glycosides, and flavonol glycosides within the plant parts, respectively. The estimation of alkaloids, saponins, in vitro antioxidant, and antibacterial activities revealed that the methanol bark extracts have high activity compared to others. Results: Total alkaloid and saponin content was found to be high in leaf methanol extract was 996.17 mg/g quinine equivalent/g and 957.3 mg/g diosgenin equivalent/g, respectively. In vitro antioxidant assays revealed a strong radical scavenging potential of the methanol bark extract against stable (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)), phosphomolybdenum, and superoxide radicals. Agar well diffusion method has been used to determine the antimicrobial activities against Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli, Acetobacter aceti, and Pseudomonas aeruginosa). Conclusion: The bark methanol extract of F. tsjahela has exhibited remarkable antioxidant activity and significant antibacterial activity (p<0.05) against all tested bacterial strains observed.